DETERMINAN PERILAKU SEKSUAL PRANIKAH PADA REMAJA PRIA DI PROVINSI KALIMANTAN BERDASARKAN ANALISIS DATA SDKI 2017 - Sari, Uswatun; Moedjiono, Apik Indarty; M. Najib Bustan (Jurnal Keolahragaan JUARA, 2022)
Premarital sexual behavior is a problem that needs attention, especially in adolescents because it is very risky to cause various kinds of health problems, such as Sexually Transmitted Infections, HIV / AIDs and even death. This study aims to determine the factors that influence sexual behavior before marriage in adolescent men aged 15-24 years in Kalimantan based on SDKI 2017 data. This study uses data from Indonesian Demographic Health Survey (SDKI) in 2017 with number of male respondents who are not married aged 15-24 years as many as 1,053 people in Kalimantan. Based on the results of the analysis using the application, it was found that out of 1,053 adolescent men, there were 81 people (7.7%) who had had sexual intercourse. There is a relationship between premarital sexual behavior in adolescent boys and knowledge of how to avoid pregnancy (p=0.000).